Efficacy and safety of low power holmium laser enucleation of the prostate: A prospective short- and medium-term single-blind randomized trial - Jungyo Suh; Min Soo Choo; Seung-June Oh (Investigative and Clinical Urology, 2023)
Purpose: We evaluated the efficacy and safety of mid-term follow-up in low-power (LP) Holmium laser enucleation of the prostate (HoLEP) compared with high-power (HP) surgery for benign prostatic hyperplasia (BPH). Materials and Methods: This prospective, single-blind, randomized controlled study was conducted between September 2020 and April 2021. Ninety male patients >50 years who underwent HoLEP for BPH were randomly assigned to HP (80 W/2 J/40 Hz) and LP (24 W/2 J/12 Hz) groups. The primary endpoint was the total International Prostate Symptom Score (IPSS) six months after surgery. The secondary endpoints were perioperative results and postoperative outcomes at two weeks, three and six months after the surgery, including Clavien–Dindo complication classification. Results: At six months after HoLEP, 41 and 42 patients were followed up in the HP and LP groups, respectively. There was no difference in the preoperative characteristics between the two groups. The prostate volumes were 67.1±23.7 mL for the HP group and 64.3±25.7 mL for the LP group (p=0.592), respectively. Although the total operative time was significantly longer by 13.1 minutes in the LP group (47.8±20.3 min vs. 60.9±23.3 min, p=0.006), the total delivered energy was significantly lower, which was only about 68% of the HP group (58.2±23.9 kJ vs. 39.9±13.2 kJ, p<0.001). Surgical outcomes significantly improved postoperatively in both groups compared to baseline, except for storage symptoms. Improvement in IPSS storage subscore was observed from the immediate postoperative 2 weeks in the LP group (8.1±3.1 to 6.9±3.8, p<0.001), whereas there was no significant recovery in the HP group (8.0±3.2 to 7.7±3.4, p=0.842). In the 6-month follow, there was no significant difference between the two groups in the IPSS total score (5.9±5.6 vs. 7.3±5.3, p=0.260) as well as IPSS storage subscore. In addition, there was no significant difference in postoperative complications, including bleeding or urinary incontinence, between the two groups. Conclusions: The HoLEP procedure performed using an LP laser device resulted in lower total delivered energy, faster recovery, and significantly improved surgical outcomes up to mid-term follow-up. There was no difference in efficiency or safety between the HP device system.